Assuring the Sustainability and Growth of Small and Medium-Sized Manufacturing Enterprises in Botswana: An Exploratory Study - Munodawafa, Tadios; Naude, Micheline; Govender, Krishna K. (International Journal of Economics and Financial Issues, 2024)
This paper explored the factors that impact the sustainability and growth of small and medium-sized manufacturing enterprises in Botswana. A self-administered structured questionnaire was used to survey 348 owners/managers of small and medium-sized manufacturing enterprises (SMEs) in the South Eastern District of Botswana. Descriptive and inferential statistics were generated from the gathered data using the Statistical Package for Social Sciences (IBM SPSS Version 27.0). findings revealed that entrepreneurial factors, firm-specific factors and exogenous factors impacted the growth and sustainability of manufacturing firms in Botswana. In addition, government policies and guidelines, innovation and creativity, human capital development, access to finance, financial management skills and managerial skills were also confirmed as significantly contributing to the growth and sustainability of manufacturing small and medium-sized enterprises in Botswana. Key recommendations derived from these findings include the need for policymakers in the government of Botswana and private sector partners to upskill owners/managers of manufacturing enterprises on business planning, financial management, financial literacy, quality management, and market research skills. Furthermore, efforts should be accelerated to promote products manufactured in Botswana to regional and global markets.